Evaluation of suitability of tube well water for irrigation in Maiduguri Metropolitan, Borno State, Nigeria - Bashir, Ali U.; Kamal, Md Rowshon; Dibal, Jibrin Musa; Kawuyo, U. A. (Academic Journals, 2017)
Groundwater contamination is gaining more concerns due to its direct and/or indirect impact on public health. Groundwaters from various sources are commonly used to irrigate vegetables in Maiduguri, Borno State. In this study, the physicochemical qualities of groundwater collected from 20 randomly selected tube wells in Maiduguri were evaluated for their suitability or otherwise for irrigation purposes. Selected wells were extensively used as sources of irrigation water. Standard procedures were followed during the analysis. The results revealed that the mean values of pH (6.6 to 8.0), calcium (2.6 to 5.2 meq/l), magnesium (2.6 to 5.0 meq/l), sodium (2.2 to 7.5 meq/l), carbonate (0.5 to 1.3 meq/l) , bicarbonate (1.8 to 5.2 meq/l), chloride ( 0.9 to 2.9 meq/l), sulphate (2.8 to 9.8 meq/l), potassium (0.3 to 0.9 mg/l), Boron (0.1 to 0.6 meq/l) and nitrogen (1.9 to 4.8 mg/l) were all found to be within the acceptable limit for suitability of water for irrigation use based on Food and Agriculture Organization (FAO) recommendations. The results further revealed that, the values of electrical conductivity (0.3 to 0.7 ds/m), total dissolved solids (192 to 448 mg/l), sodium adsorption ratio (0.40 to 3.62), residual sodium carbonate (-1.3 to -7.6 meq/l), magnesium adsorption ratio (35.80 to 49.06%) and Kelly ratio (0.10 to 0.90) of the samples were within the safe limit recommended for irrigation water use. The quality of tube well waters in the study area can thus be regarded as good, and suitable for irrigation purposes, but similar analysis should be conducted on a routine basis to monitor the qualities of the waters toward safeguarding public health.